Blockchain Based Donation Management in Disaster Response - K C, Ankit (Journal of Innovation Information Technology and Application (JINITA), 2024)
Both natural and man-made disaster leave thousands of people in vulnerable and in need for essential aid. While individuals generously donate resources, traditional donation management systems suffer from limitations. Centralized control, opaque transactions, and potential corruption often hinder aid delivery and leave victims in despair. This paper proposes a novel Ethereum blockchain-based system for transparent and secure disaster donation management. Utilizing smart contracts, the system ensures traceability, accountability, and immutability of donations, empowering donors and fostering trust. This paper presents the system's architecture, detailing its components and interactions through sequence diagrams and algorithms. Additionally, successful testing on the Sepolia Ethereum testnet validates its functionality. To assess its effectiveness, a cost and security analysis is conducted. This blockchain-based framework offers a promising solution for transparent and efficient disaster response, potentially revolutionizing donation management. Further research, particularly on donation allocation optimization within the system holds immense potential for future development.